Virilisation during Pregnancy in a Patient with Metastatic Colorectal Cancer. (14th October 2012) - Conway, F.; Jarvis, S.; Thornton, M.
Abstract : This paper describes the case of a 25-year-old woman with virilisation occurring during pregnancy in the presence of metastatic colorectal cancer. Virilisation during pregnancy is rare. The potential causes include adrenal, foetal, or ovarian pathologies. The most common causes during pregnancy are pregnancy luteoma and hyperreactio luteinalis. The incidence of cancer during pregnancy is rare and the incidence of colorectal cancer (CRC) in pregnancy is even rarer. The presenting signs and symptoms of CRC can be confused with symptoms commonly encountered during pregnancy, thereby delaying diagnosis and commencement of treatment. Diagnosis and staging also proves more problematic in the pregnant patient as the usual modalities of colonoscopy with biopsy and imaging with CT are relatively contraindicated. Treatment is dependent on gestational age of the foetus. There is currently no agreed best practice as to the role of prophylactic oophorectomy in the prevention of metachronous ovarian metastases. Surgical and adjuvant treatments have implications for females of child-bearing age.